Identification of four novel variants in the CDH23 gene from four affected families with hearing loss - Kang, Baoling; Lu, Xinshu; Xiong, Jianjun; Li, Yuan; Zhu, Jinwen; Cai, Tao (Frontiers in Genetics, 2022)
Background: Hearing loss (HL) is the most common form of sensory disorder in humans. Molecular diagnosis of HL is important for genetic counseling for the affected individuals and their families. Methods: To identify potential genetic causes, we performed whole-exome sequencing and related biomedical informatics for 351 non-syndromic HL patients and their family members. Results: In the present study, we report the identification of four compound heterozygous variants in the CDH23 gene from four affected families, including four novel variants (c.995C>A, p.T332K; c.2159G>A, p.R720Q; c.5534A>G, p.N1845S and c.7055-1G>C) and two frequently reported variants (c.719C>T, p.P240L and c.4762C>T, p.R1588W). Conclusions: Our findings significantly expanded the mutation spectrum of CDH23-associated autosomal recessive hearing loss.